Automated right ventricular strain by speckle tracking echocardiography in patients with systemic scleroderma. (3rd October 2022) - Tsoukas, A; Koutsogiannaki, E; Giannakopoulou, I; Gioti, O; Iliopoulos, D; Saad, R; Chalkitis, V; Peteinaki, A; Karapedi, E; Papaioannou, N
Abstract: Introduction: In patients with scleroderma the morphological remodeling and alteration of right ventricular (RV) function begins even before the setting of pulmonary artery hypertension (PAH). These alterations are associated with worse outcomes and high mortality. Purpose: Early detection of RV dysfunction is possible using advanced imaging techniques and can lead to specific therapeutic measures before installation of PAH. Purpose of this study is to evaluate new indices, based on speckle tracking technology, for identification of subclinical RV systolic failure. Methods: Twenty-five (25) scleroderma patients without any signs or symptoms of PAH and twenty-five (25) healthy subjects were included in the present study. Two-dimensional echocardiography (2DE) and two-dimensional speckle-tracking echocardiography (2DSTE) were performed. All the usual 2DE, Doppler and tissue Doppler imaging measurements were obtained for the evaluation of RV function. Moreover, TAPSE, maximum systolic myocardial velocity from TDI of lateral tricuspid valve annulus (SRV), auto RV global longitudinal strain (aRVGLS) and auto RV free wall longitudinal strain (aRVFWLS) by 2DSTE were measured. aRVGLS is a new index, with appropriate RV function echo logistics in new technology echo systems, independent from known manual measurements. Results: In scleroderma patients significantly higher systolic pulmonary artery pressure was recorded, although it remained within normal limits in both groups. Scleroderma patients had significant decreased RV systolic function with significantly lower TAPSE and SRV. Both aRVGLS and aRVFWLS were also significantly lower in scleroderma patients compared to the control group. aRVGLS was the best predictor of early RV systolic impairment in patients with scleroderma. Conclusions: Scleroderma is a severe systematic disease associated with high mortality rates. RV remodeling, dysfunction, and progressive pulmonary artery hypertension are among the most important internal organ manifestations of this disease. Early detection of RV dysfunction is possible by 2DSTE, and may be helpful to guide further therapy in these patients. Funding Acknowledgement: Type of funding sources: None.